(Nl)QÆTERATURNO(B-(NMISTECXKA sTOROVINE^^INA (B:s)E (NDOW)QÆDNIK (B/s)E - (NsTOROVIN(B. (NRAJDERVADM)QÆN(B..s)E; (NsTOROVIN(B. (NCENTRAL)QÆZOWANA BÆBL(B. (NSISTEMA(B.s)E ((N~ERN)QÆWCÆ (B:s)E (NpRUT(B,s, 2006)
(NdOW)QÆDNIK ROZKRIWAÃ VITTÃWIJ Æ TWOR^IJ [LQH WÆDOMIH LÆTERATORÆW(B, (NMITCÆW(B, (NQKÆ PEREBUWALI(B, (NNARODILISQ(B, (NVILI J TEPER VIWUTX U sTOROVINECXKOMU RAJONÆ Æ SWOÃ@ TWOR^ÆST@ ZBAGATILI DUHOWNU SKARBNIC@ bUKOWINSXKOGO pÆDGÆR(B'(NQ(B.s)E
Keywords: (Nl)QÆTERATUROZNAWSTWOs)E -- (NuKRA)QÇNSXKA LÆTERATURAs)E -- (NdOW)QÆDKOWÆ WIDANNQs)E -- (N~ERN)QÆWECXKA OBLASTX (B((NuKRAÇNA(B)s)E -- (NsTOROVINECXKIJ R(B-(NN (B((N~RW(B).s; (NdOW)QÆDKOWÆ WIDANNQs)E -- (NdOW)QÆDNIKI(B.s)E; (N~ERN)QÆWECXKIJ AWTOR(B.s)E